2007
DOI: 10.1287/mksc.1060.0253
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Product Variety on Brand Perception and Choice

Abstract: We propose that the variety a brand offers often serves as a quality cue and thus influences which brand consumers choose. Specifically, brands that offer a greater variety of options that appear compatible and require similar skills tend to be perceived as having greater category expertise or core competency in the category, which, in turn, enhances their perceived quality and purchase likelihood. Six studies support this proposition and demonstrate that compared to brands which offer fewer products, (a) bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(134 citation statements)
references
References 39 publications
7
123
0
4
Order By: Relevance
“…For example, wearing a formal lab coat, as done in the (in)famous Milgram obedience experiments, enhances credibility and respect (Burger 2009). Further, work in marketing shows that credibility cues serve as an effective tool to improve perceptions of competence (Moscarani 2007) and in so doing can increase purchase likelihood (Berger, Draganska, and Simonson 2007) and choice (Erdem and Swait 2004). Thus, we hypothesize that a credibility cue will increase perceptions of competence, which should benefit perceptions of nonprofit companies in particular (as they would otherwise be predicted to be viewed as low in competence).…”
Section: H4mentioning
confidence: 93%
See 1 more Smart Citation
“…For example, wearing a formal lab coat, as done in the (in)famous Milgram obedience experiments, enhances credibility and respect (Burger 2009). Further, work in marketing shows that credibility cues serve as an effective tool to improve perceptions of competence (Moscarani 2007) and in so doing can increase purchase likelihood (Berger, Draganska, and Simonson 2007) and choice (Erdem and Swait 2004). Thus, we hypothesize that a credibility cue will increase perceptions of competence, which should benefit perceptions of nonprofit companies in particular (as they would otherwise be predicted to be viewed as low in competence).…”
Section: H4mentioning
confidence: 93%
“…Extant research shows that sources vary on credibility, which has a significant impact on persuasion (e.g., Berger et al 2007;Sternthal, Dholakia, and Leavitt 1978 M p 22 male) at Stanford were randomly assigned to one of the four conditions comprising the 2 (organization type: for-profit vs. nonprofit) # 2 (endorsement credibility: high vs. low) between-subject design. Participants were first presented with three ecofriendly laptop bags sold by World of Good.…”
Section: Pretestmentioning
confidence: 99%
“…Yet, while researchers analyzing actual field data have reported some instances in which sales actually went up with fewer options, in many cases, reducing the number of different items apparently led to reduced sales or to no change (Boatwright and Nunes 2001;Borle et al 2005;Drèze, Hoch, and Purk 1994;Sloot, Fok, and Verhoef 2006). In line with this, in a series of experiments, Berger, Draganska, and Simonson (2007) showed that introducing finer distinctions within a product line increased perceptions of quality and that a brand offering high variety within a category has a competitive advantage.…”
Section: Arguments Against the Choice Overload Hypothesismentioning
confidence: 95%
“…They also allow customers to seek variety and maintain flexibility during the purchase process (Simonson 1990). Moreover, the variety of products offered by a specific brand is perceived as a cue for the quality of the brand (Berger et al 2007). In other words, larger item sets are often perceived to be more attractive.…”
Section: Attractiveness and Choice Difficulty In Large Item Setsmentioning
confidence: 99%